Pengembangan Media Pembelajaran Movie Learning Berbasis Augmented Reality - Ashari, Sri Ayu; A, Hermila; Mappalotteng, Abdul Muis (Universitas Negeri Gorontalo, 2022)
The application of media to support teaching and learning activities that are less attractive can have an impact on low motivation and enthusiasm for student learning in the learning process. This problem was encountered when learning WAN-based Technology subjects in class XI of the Computer and Network Engineering expertise program at SMK Darussalam Makassar. For this reason, the development of Movie Learning media based on Augmented Reality needs to be developed to overcome these problems. The objectives of this study are (1) to determine the stages of learning media development, (2) to determine the valid criteria for learning media, and (3) to determine the practicality of learning media developed on WAN broad-based technology competencies. The development procedure used is the ADDIE development model. This learning media is based on movie learning, which was developed and validated by two experts and revised to make results suitable for use. The results of this study show that (1) the learning media developed is declared valid and suitable for use in the learning process, and (2) the implementation of the learning media developed is practical and easy to use.Penerapan media pendukung kegiatan belajar mengajar yang kurang menarik dapat berdampak pada rendahnya motivasi dan semangat belajar siswa dalam proses pembelajaran. Permasalahan tersebut ditemui dalam pembelajaran mata pelajaran Teknologi berbasis WAN di kelas XI program keahlian Teknik Komputer dan Jaringan di SMK Darussalam Makassar. Untuk itu, pengembangan media pembelajaran Movie Learning berbasis Augmented Reality perlu dilakukan untuk mengatasi masalah tersebut. Tujuan penelitian ini adalah: (1) untuk mengetahui tahapan pengembangan media pembelajaran, (2) untuk mengetahui kriteria valid media pembelajaran, (3) untuk mengetahui kepraktisan media pembelajaran yang dikembangkan pada kompetensi teknologi berbasis luas WAN. Prosedur pengembangan yang digunakan adalah model pengembangan ADDIE. Media pembelajaran ini berbasis Movie learning yang dikembangkan divalidasi oleh 2 orang ahli dan mengalami revisi sehingga didapatkan hasil yang layak digunakan. Hasil penelitian ini menunjukan bahwa: (1) media pembelajaran yang dikembangkan dinyatakan valid dan layak untuk digunakan dalam proses pembelajaran, (2) implementasi media pembelajaran yang dikembangkan bersifat praktis dan mudah digunakan.